ANTIPLASMODIAL ACTIVITY OF APORPHINE ALKALOIDS FROM Rollinia pittieri AND Pseudomalmea boyacana (ANNONACEAE) - Edison J. OSORIO D. (Universidad de Antioquia, 2009)
<!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} @font-face {font-family:Aldine401BT-RomanA; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"MS Mincho"; mso-font-charset:128; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 134676480 16 0 131073 0;} @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} @font-face {font-family:"\@Aldine401BT-RomanA"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:128; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:0 134676480 16 0 131072 0;} @font-face {font-family:TimesNewRomanPS-ItalicMT; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0;} @font-face {font-family:SymbolMT; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"MS Mincho"; mso-font-charset:128; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:1 134676480 16 0 131072 0;} @font-face {font-family:"\@SymbolMT"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:128; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:0 134676480 16 0 131072 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} @page Section1 {size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> In the course of from ethnobotanical or chemotaxonomical studies on biologically active substances with antiparasitic effects from Anonaceae colombian plants, substantial antiplasmodial activity was observed from the ethyl acetate extract of the stem of Rollinia pittieri and Pseudomalmea boyacana (Annonaceae), the alkaloids isolated from these were studied. Of the alkaloids, liriodenine exhibited the highest activity against chloroquine sensitive and chloroquine resistant strains of Plasmodium falciparum (CI50 = 8.0-10.0 μg/ml). In addition, inhibition of β-hematin formation (If????-h) by isolated compounds was evaluated (Ifs-h). O-methylmoschatoline and melosmine showed inhibition percentage >96% at 2 mg/ml. Some degree of cytotoxic to U-937 cells activity was observed by oxoporphine alkaloids.